2018
DOI: 10.3389/fnbeh.2018.00058
|View full text |Cite
|
Sign up to set email alerts
|

Altered Brain Excitability and Increased Anxiety in Mice With Experimental Colitis: Consideration of Hyperalgesia and Sex Differences

Abstract: Crohn’s disease (CD) and ulcerative colitis (UC) are incurable lifelong inflammatory bowel diseases (IBD) with a rising worldwide incidence. IBD is characterized by diarrhea, rectal bleeding, severe cramping and weight loss. However, there is a growing evidence that IBD is also associated with anxiety- and depression-related disorders, which further increase the societal burden of these diseases. Given the limited knowledge of central nervous system (CNS) changes in IBD, we investigated CNS-related comorbiditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 61 publications
19
43
0
Order By: Relevance
“…This also reinforces our previous findings showing that there are no differences in the ambulatory behavior of mice treated with luteolin as assessed in the open field test [7]. Altogether, our data indicate that DSS induces anxiety like behaviors that are consistent with previous findings in both male and female mice [5] and which can be attenuated by luteolin treatment.…”
Section: Main Textsupporting
confidence: 93%
See 1 more Smart Citation
“…This also reinforces our previous findings showing that there are no differences in the ambulatory behavior of mice treated with luteolin as assessed in the open field test [7]. Altogether, our data indicate that DSS induces anxiety like behaviors that are consistent with previous findings in both male and female mice [5] and which can be attenuated by luteolin treatment.…”
Section: Main Textsupporting
confidence: 93%
“…Peripheral inflammation is recognized as an important contributor to anxiety [1] and major depressive disorder [2], with such symptoms observed particularly among patients with inflammatory bowel disease (IBD) [3, 4]. Recent rodent studies using the dextran sodium sulfate (DSS) model demonstrated that the activation of the immune system contributes to the development of anxiety- and depression-related behaviors as consequence of colitis [57]. In our previous work, we showed that long-term behavioral abnormalities related to anxiety and depression arise in mice of either sex as a consequence of acute colonic inflammation, in parallel with a marked elevation of interleukin 1beta in the hippocampus, increased infiltration of leukocytes into the brain microvasculature and significant changes of the firing properties of hippocampal pyramidal cells.…”
Section: Main Textmentioning
confidence: 99%
“…Individual mice were placed in the EPM center and allowed to move freely for 5 min. The test was video recorded and later analyzed for time spent in the open versus closed arms, as previously described (Acharjee et al, 2013, Nyuyki et al, 2018, Pellow et al, 1985).…”
Section: Methodsmentioning
confidence: 99%
“…Acute colitis by DSS impairs cognitive [20] and locomotive behavior [21], and has been shown to induce hyperalgesia [9, 22], which can further modify mouse behavior. To determine whether fluid supplementation reduces mouse stress during acute colitis, DSS-treated control and fluid-supplemented mice underwent the TST, NOR, and open field activity tests on the indicated days (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%